Let's talk about adaptation! How individuals discuss adaptation during evidence-based practice implementation. Issue 4 (28th November 2019) - Lengnick-Hall, Rebecca; Fenwick, Karissa; Hurlburt, Michael S.; Green, Amy; Askew, Rachel A.; Aarons, Gregory A.
Abstract : Purpose: Researchers suggest that adaptation should be a planned process, with practitioners actively consulting with program developers or academic partners, but few studies have examined how adaptation unfolds during evidence-based practice (EBP) implementation. The purpose of this paper is to describe real-world adaptation discussions and the conditions under which they occurred during the implementation of a new practice across multiple county child welfare systems. Design/methodology/approach: This study qualitatively examines 127 meeting notes to understand how implementers and researchers talk about adaptation during the implementation of SafeCare, an EBP aimed at reducing child maltreatment and neglect. Findings: Several types of adaptation discussions emerged. First, because it appeared difficult to get staff to talk about adaptation in group settings, meeting participants discussed factors that hindered adaptation conversations. Next, they discussed types of adaptations that they made or would like to make. Finally, they discussed adaptation as a normal part of SafeCare implementation. Research limitations/implications: Limitations include data collection by a single research team member and focus on a particular EBP. However, this study provides new insight into how stakeholders naturally discuss adaptation needs, ideas and concerns. Practical implications: Understanding adaptation discussions can help managers engage frontline staff who are using newly implemented EBPs, identify adaptation needs and solutions, and proactively support individuals who are balancing adaptation and fidelity during implementation. Originality/value: This study's unique data captured in vivo interactions that occurred at various time points during the implementation of an EBP rather than drawing upon data collected from more scripted and cross-sectional formats. Multiple child welfare and implementation stakeholders and types of interactions were examined.